Gastric Cancer in the Excluded Stomach 10 Years after Gastric Bypass - Augusto Tinoco; Lorena F. Gottardi; Eduardo D. Boechat (Case Reports in Surgery)
According to the Brazilian health authorities, around 2,000 new cases of gastric cancer emerge in Brazil per year (Instituto Nacional de Câncer José Alencar Gomes da Silva, 2014). Indeed, gastric cancer constitutes the second most common cause of cancer-related mortality worldwide and 95% of such malignancies are adenocarcinomas (De Roover et al., 2006, and Clark et al., 2006). Roux-en-Y gastric bypass (RYGB) is a procedure frequently employed in bariatric surgery but restricted access to the excluded stomach means that discovery of gastric lesions is difficult, and diagnosis and treatment may be delayed. We report herein a case of gastric adenocarcinoma in the excluded stomach of a patient submitted to RYGB with the purpose of illustrating the difficulty of diagnosing and treating this rare condition.